On the Influence of Different Perspectives on Evaluating the Teamwork Quality in the Context of Agile Software Development - Silva, Manuel; Freire, Arthur; Perkusich, Mirko; Gorgônio, Kyller; Almeida, Hyggo; Perkusich, Angelo (Anais do Simpósio Brasileiro de Engenharia de Software (SBES), 2020)
Background: The literature reports that different perspectives (i.e., roles) within an agile software development team (ASD) perceive the impact of teamwork quality (TWQ) on team performance in different ways. However, nothing is said about the perspective influence on the assessment TWQ construct itself. Aims: To fill this gap, this study provides a more in-depth insight into how the perspective affects the perception of the variables in TWQ construct. Method: We performed a comparative analysis in which we collected TWQ-related data from 21 ASD teams from 2 software development companies. We interviewed 130 professionals from different roles (i.e., developers, technical leader, and manager). We compared the results for the associated perspectives using the Mean Relative Error (MRE). Results: The leader and manager perspectives show reasonable agreement when evaluating three variables that compose the TWQ (i.e., Cohesion, Self-Organizing, and Team Orientation). Developers and managers strongly agreed on four variables (i.e., Communication, Cohesion, Self-Organizing, and Collaboration). For developers and leaders, only the Coordination variable showed reasonable agreement. Conclusions: We believe that more studies are needed to generalize the results. However, the research indicates that different perspectives evaluate the variables that compose the TWQ construct in different ways. Closer discussions and definitions of more objective metrics are advisable to assess these variables, aiming to align expectations between perspectives and consensus when measuring efforts to achieve continuous improvement team's.